HAK TERSANGKA/TERDAKWA DALAM MEMPEROLEH PERAWATAN MEDIS YANG LAYAK DI INDONESIA DAN BELANDA: The Rights of Suspects/Defendants to Obtain Proper Medical Treatment in Indonesa and The Netherlands - Putri Warna Medi Awi; Gandes Candra Kirana (Reformasi Hukum Trisakti, 2025)
Health is a fundamental human right that must be protected by the state. This presents a significant challenge for countries like Indonesia and the Netherlands in upholding human rights, particularly regarding the provision of proper medical care for suspects/defendants. This study addresses main issue: the regulation of the right of suspects/defendants to receive adequate medical care in Indonesia and the Netherlands.The research aims to identify and analyze the legal framework governing this right. A normative approach with a descriptive-analytical method is used, based on literature review and comparative legal analysis. Data sources include primary and secondary legal materials. The result and the conclusion show that Indonesia regulates this right through the Criminal Procedure Code (KUHAP) and Undang-Undang Nomor 22 of 2022, while the Netherlands addresses it in the Penitentiaire Beginselenwet (Penitentiary Principles Act). Although both countries have legal provisions, they face challenges in implementation, particularly in safeguarding human rights and the presumption of innocence. This research is expected to serve as a reference for strengthening the protection of suspects’/defendants’ rights in Indonesia and to offer insights into international practices.